RELIGIUSITAS PEMENTASAN TARI BARIS KUPU-KUPU PADA UPACARA PUJAWALI DI PURA DALEM DASAR BANJAR SEMA DESA PAKRAMAN BUNGKULAN KECAMATAN SAWAN KABUPATEN BULELENG - Wisnawa, Dewa Ketut (Institut Hindu Dharma Denpasar, 2018)
Bali is an island rich in cultural and religious art. One of the most famous religious artworks in Bali is the Butterfly Row Dance. Butterfly Row Dance is a sacred dance that is only found in Buleleng Bungkulan village. This study aims to find out in detail how the staging structure, means of staging, history, values and tingkan religiosity of society in the village of Bungkulan. Based on the results of the research, it is known that the Butterfly Dance has several religious aspects such as the purification aspect, the aspect of expression of gratitude, the cultural aspect, the aesthetic aspect of the religious, the sociological aspect, the aspect of pleading fertility. In addition, Butterfly Rice Dance contains the implications of high religious values such as Tri Hita Karana Implication, bhakti attitude implications, sociocultural implications, aesthetic implications, sacred implications, leadership implications, tatwa implications, ethical implications, psychological implications, and the implications of religiosity.